2021
DOI: 10.1101/2021.01.30.181370
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Moving outside the lab: The viability of conducting sensorimotor learning studies online

Abstract: Collecting data online via crowdsourcing platforms has proven to be a very efficient way to recruit individuals from a large diverse sample. While many fields in psychology have embraced online studies, the field of motor learning has lagged behind. We suspect this is because of an implicit assumption that the loss of experimental control with online data collection will be problematic for kinematic data. As a first foray to bring motor learning online, we developed a web-based platform to collect kinematic da… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 103 publications
(175 reference statements)
4
25
0
Order By: Relevance
“…That said, our data are typical of many previous lab-based visuomotor adaptation studies, with comparable levels of final performance (Huberdeau et al, 2015;Morehead, Qasim, Crossley, & Ivry, 2015;Vaswani et al, 2015;Neville & Cressman, 2018;Weightman et al, 2020;Weightman, Brittain, Miall, & Jenkinson, 2021). Furthermore, initial evidence suggests that kinematic data and results from online motor learning studies are analogous with those collected in a controlled lab environment (Tsay, Lee, Ivry, & Avraham, 2021) and that online tasks perform well in terms of accuracy and precision with regards to timing of visual stimuli and response capture (Bridges, Pitiot, MacAskill, & Peirce, 2020).…”
Section: Discussionsupporting
confidence: 77%
“…That said, our data are typical of many previous lab-based visuomotor adaptation studies, with comparable levels of final performance (Huberdeau et al, 2015;Morehead, Qasim, Crossley, & Ivry, 2015;Vaswani et al, 2015;Neville & Cressman, 2018;Weightman et al, 2020;Weightman, Brittain, Miall, & Jenkinson, 2021). Furthermore, initial evidence suggests that kinematic data and results from online motor learning studies are analogous with those collected in a controlled lab environment (Tsay, Lee, Ivry, & Avraham, 2021) and that online tasks perform well in terms of accuracy and precision with regards to timing of visual stimuli and response capture (Bridges, Pitiot, MacAskill, & Peirce, 2020).…”
Section: Discussionsupporting
confidence: 77%
“…As such, this method eliminates the potentially confounding effects of strategic processes (McDougle et al, 2016; Kim et al, 2020). Nonetheless, participants’ reach angles gradually shift in the direction opposite to the clamp and shows the cardinal signatures of implicit motor adaptation without awareness (Morehead et al, 2017; Kim et al, 2018, 2019; Parvin et al, 2018; Tsay et al, 2020a, 2020b, 2021a, 2021b; Avraham et al, 2021; Poh et al, 2021; Vandevoorde and Orban de Xivry, 2019; Yin and Wei, 2020).…”
Section: Resultsmentioning
confidence: 96%
“…Given that attenuation of implicit adaption in relearning has not been highlighted in the literature, we conducted a replication study using an online platform [32,33], one in which the crowdsourced participants complete the study remotely using their individual display and response devices. The results from the online study were quite similar to those observed in Experiment 2 (S2 Fig, all statistics are reported in the caption).…”
Section: Plos Biologymentioning
confidence: 99%
“…Based on power calculations from the aftereffect data in Experiment 2, a minimum sample size of 9 would be required (d = 0.94). However, given the results from pilot work indicating that online data would be more variable and show a lower asymptotic level of adaptation [33], we opted to use a large sample size.…”
Section: Plos Biologymentioning
confidence: 99%